Metered and Unmetered Billing: How Asymmetric are the Phcn Bills? - Ofonyelu, C Chris; R. E, Eguabor (Journal of Social Economics Research, 2014)
This study provides evidence on the existence of asymmetries in the metering of electricity by the Power Holding Company of Nigeria (PHCN) between January 2005 and November, 2013.Using Chiappori-Salanie correlation statistics and data from the response of 720 electricity consumers and 524 PHCN bills within the Benin Electricity Distribution Company, the study observed that the electricity bills were asymmetric. The asymmetries were observed for both the metered and unmetered consumers over the period. For the metered consumers, the asymmetry was more prevalent for the analogue than the prepaid meter users. The asymmetry existed mainly through procurement of meter in the case of the prepaid meter users. The study argues that estimated billings by the PHCN give room for asymmetry and overprices energy consumptions. The study suggests a prepaid metering of all electricity consumers in Nigeria.